1998
DOI: 10.3758/bf03211931
|View full text |Cite
|
Sign up to set email alerts
|

Signal detection comparisons of phonemic and phonetic priming: The flexible-bias problem

Abstract: The phonemic priming effect may reflect the hidden dynamics of spoken word perception and has thus been a key topic of recent research. This investigation compared phonemic and phonetic priming (cf. Goldinger, Luce, Pisoni, & Marcario, 1992), using signal detection methods. Although these methods were intended to provide separate indices of sensitivity and bias changes, the results were more complex. Instead, phonemic priming engendered a flexible, trial-specific strategy that affected hits and false alarms (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The best course of action that one could take would be to incorporate into the experimental design manipulations that counteract such strategies. Goldinger (1998Goldinger ( , 1999) suggests a few possibilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The best course of action that one could take would be to incorporate into the experimental design manipulations that counteract such strategies. Goldinger (1998Goldinger ( , 1999) suggests a few possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…In two studies using multiple tasks but not shadowing, Goldinger et al (1992; see also Goldinger, 1998) found converging evidence that the RT advantage in the 1-and 2-overlap conditions is due to response bias. One of the most convincing demonstrations of this came from a series of lexical decision experiments in which the interstimulus interval (ISI) between prime and target and the percentage of trials on which the prime and target were phonologically related (PRP) were varied, two manipulations effective in past work at reducing the influence of response biases (Neely, 1977(Neely, , 1991Posner & Snyder, 1975).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Subjects appear to learn that target words are likely to begin with the same segments as their primes; hence, they prepare the production of those segments and, thus, repeat the targets more rapidly (Goldinger, 1999;Hamburger & Slowiaczek, 1999). The effect is not observed in the lexical decision task (Radeau, Morais, & Dewier, 1989;Slowiaczek & Hamburger, 1992;Slowiaczek & Pisoni, 1986), except when materials are presented in noise and a relativelyhigh proportion of related trials is included (Goldinger, 1998b;Goldinger, Luce, Pisoni, & Marcario, 1992). Again, Goldinger et al (1992) explained the facilitation they observed in terms of bias: Expectations of shared initial segments between primes and targets could benefit performance on targets in noise even when no naming response is required.…”
mentioning
confidence: 88%
“…It is much less clear how such a bias would influence shadowing performance, where the naming response varies from trial to trial. If the bias acted at the response stage, influencing the speech production processes required for a naming response, it would have to be flexible, in the same sense as the strategy proposed by Goldinger (1998b) for single-phoneme onset overlap facilitation. That is, the bias would need to be reapplied on each trial, so that the encoding of the phonologicalmaterial for each particular target word could be benefited in some way by the presence of rhyme overlap.…”
Section: Rhyme Biasmentioning
confidence: 99%